PENGARUH MODEL PENYELENGGARAAN WORK-BASED LEARNING ROLLING TERPADU TERHADAP ASPEK-ASPEK KUALITAS HASIL BELAJAR - Budi Tri Siswanto (Jurnal Pendidikan Teknologi dan Kejuruan, 2012)
ABSTRACTThis reseach aims at (1) revealing the influence of integrated and Rolling Work Based Learning (WBL)implementation towards the quality of WBL learning result (2) obtaining the data of the output aspects for thequality of WBL learning results in the vocational education program of Automotive DIII.This research belongs to experimental research in the study program of Automotive DIII. This research wasconducted in trainning centre on several brand owner agent of Automotive area in Jakarta, Karawang, Tangerang,Bekasi. The population of the research was the students of Diploma III of Automotive Engineering Study Programwho were conducted field or industrial practicum. The research sample was two groups of students consisted of 50students for each group who come from 3 state universities and 3 private universities in Yogyakarta and CentralJava. This experimental study was conducted from July till October 2012 with factorial design of 2 x 1. The datacollection techniques were using inventory, observation sheets, and documentation. The analysis of content validitywas conducted by expert judgement. The construct validity was using factor analysis and item realibility with AlphaCronbach and KR-20. Meanwhile, the hypothesis testing was conducted by ANAVA technique and T-Test with theassistance of SPSS 17 program.The results of the research showed that (1) the implementation of Integreted and Rolling WBL (industrial/field practicum) influenced the result of WBL learning result, (2) the output aspects of WBL learning result were theimprovement of automotive mechanical knowladge, professionalism, readiness, and students’ autonomy.Keywords: integrated and Rolling Work Based Learning (WBL), quality of WBL learning result